Business Participation in the Implementation of Child-Friendly City Policy in Depok City - Adibrata, Muhammad Arjuna; Purwanto, Agus Joko; Rulinawati, Rulinawati (International Journal of Law Policy and Governance, 2023)
The implementation of child-friendly city policies plays a pivotal role in ensuring the well-being and optimal development of children within urban environments. This article explores the significant involvement of the business sector in supporting the implementation of child-friendly city policies in the context of Depok City. The engagement of the business sector, facilitated by the Association of Indonesian Child-Friendly Companies (Asosiasi Perusahaan Sahabat Anak Indonesia or APSAI), along with the principles of Corporate Social Responsibility (CSR), forms a crucial partnership with the government and the community to create an environment that nurtures the growth of children. This article discusses the multifaceted contributions of the business sector, focusing on financial investments, infrastructural development, educational initiatives, and collaborative efforts aimed at enriching the lives of children in Depok City. It delves into the model of Van Meter and Van Horne (1975) to analyze the factors influencing the implementation of child-friendly policies and elaborates on the distinctive roles APSAI and CSR play in supporting this endeavor. By examining these roles comprehensively, the article underscores how collaborative efforts among the government, the community, and the business sector can holistically foster a city that prioritizes the rights and well-being of its youngest inhabitants. Ultimately, this article highlights the significance of leveraging business resources, expertise, and commitment to contribute to the realization of a child-friendly urban environment. It underscores the importance of fostering partnerships, effective communication, and continuous coordination between these stakeholders to ensure the successful implementation and sustainability of child-friendly city policies in Depok City